A theory-driven framework for the design and implementation of successful agri-environmental programmes: results of a realist review - Bibi Witvliet; Huub Ploegmakers; Sander Meijerink (International Journal of Agricultural Sustainability)
In order to tackle biodiversity decline, various Agri-Environmental Programmes (AEPs) have been established in intensive farming countries. Farmers play a crucial role in restoring biodiversity. Therefore, understanding farmers’ participation in AEPs is of vital importance. Yet, a theory-driven understanding of what AEP strategies need to be implemented in which context to motivate farmers to work on AEPs is lacking. We aimed to close this gap by identifying Programme Theories (PTs) for the design and implementation of successful AEPs. We performed a realist review to identify causal relationships between agri-environmental strategies (S), their outcomes (O), and the contextual factors (C) and motivational mechanisms (M) that explain how, when and why AEP outcomes were achieved. The identified strategy-context-mechanism-outcome (SCMO) configurations and underlying theories were clustered on the C–M relationship to develop PTs. 47 studies were included. Based on the available evidence on more than 60 AEPs in 17 intensive farming countries, 10 interrelated PTs were identified. These 10 PTs form a theory-driven framework that summarizes the insights into how, when and why farmers work on successful AEPs. Each PT provides practical insights into the agri-environmental strategies and necessary contextual factors and mechanisms to guide farmers’ behavioural change toward biodiversity conservation.